2016
DOI: 10.21093/ijeltal.v1i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Process Based Approach towards Students’ Creativity in Writing English Paragraph

Abstract: Abstract:The research entitled "Process based Approach towards Students

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Noor (2016) found that some students had negative attitude about writing or lack confidence to write something. Qomariyah & Permana (2016) also found that majority students to present correct topics for their paragraph which are often incomplete sentences rather than phrases. The students' paragraph topic statements are not appropriately stated yet; they are mostly not in response to the topics proposed.…”
Section: E Discussionmentioning
confidence: 89%
“…Noor (2016) found that some students had negative attitude about writing or lack confidence to write something. Qomariyah & Permana (2016) also found that majority students to present correct topics for their paragraph which are often incomplete sentences rather than phrases. The students' paragraph topic statements are not appropriately stated yet; they are mostly not in response to the topics proposed.…”
Section: E Discussionmentioning
confidence: 89%
“…PBI model restricts students to elaborate their ideas in certain topics being to write. It is reinforced by Qomariyah and Permana [52] who state that the PBI model can help preservice teachers arrange a simple paragraph, but students are still difficulties in composing sentences into complete texts of descriptive texts or narrative texts. Based on the research finding in the control group, the preservice teachers' creativity doesn't give a significant effect to improve students' achievement in writing class.…”
Section: Results and Discussion 41 Research Findingsmentioning
confidence: 99%
“…As students engage in sentencecombining activities, they learn how to vary sentence structure in order to change meaning and style. Some researchers suggest that the appropriate techniques of writing should be implemented (Qomariyah & Permana, 2016;Noor, 2016;Ariyanti, 2016;Omar & Ghazali, 2016;Nurhayati, 2016;Setyowati, 2016;Lirola & Irwin, 2016). Shaughnessy (1977) and Hillocks (1986) suggest that sentence combining is an effective method to improve writing.…”
Section: E Discussionmentioning
confidence: 99%